Bradycardia unresponded to atropin testing was successfully treated with therapeutic plasma exchange in a patient with severe COVID-19 complicated by Guillain-Barré syndrome: A case report - Duong-Quy, Sy; Huynh-Truong-Anh, Duc; Tran-Xuan, Quynh; Nguyen-Quang, Tien; Nguyen-Thi-Kim, Thanh; Nguyen-Chi, Thanh; Tran-Ngoc-Anh, Thuy; Nguyen-Van-Hoai, Nam; Do-Thi-Thu, Mai; Tang-Thi-Thao, Tram; Bui-Diem, Khue; Hoang-Anh, Tien; et al. (Frontiers in Cardiovascular Medicine, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has been an alarming situation worldwide for the past 2 years. The symptoms of coronavirus disease 2019 (COVID-19) are not only confined to the respiratory system but also affect a multitude of organ systems. Bradycardia associated with Guillain-Barré syndrome (GBS) is a rare autonomic and peripheral neurological complication of COVID-19. In this case report, we present the case of a 26-year-old man diagnosed with bradycardia associated with GBS after contracting COVID-19. Initially, this patient had the classical symptoms of COVID-19 and was hospitalized in the intensive care unit (ICU) for acute respiratory distress syndrome (ARDS). Then, he developed weakness in the lower extremities, diminished tendon reflexes, a loss of sensation without sphincter muscle disorders, and bradycardia. His bradycardia did not respond to atropine. The patient was treated concurrently with a high-flow nasal cannula, systemic corticosteroids, anticoagulation, and therapeutic plasma exchange (TPE) for COVID-19-induced ARDS, bradycardia, and GBS. His ARDS and bradycardia improved after the first cycle of TPE and medical treatment. After three cycles of TPE, the patient progressively recovered his muscle strength in the lower limbs and regained peripheral sensation. He was discharged from the hospital in stable condition after 4 weeks of hospitalization and was followed up after 6 months for cardiorespiratory and neurological complications. This case report elucidates the potential difficulties and challenges that physicians may encounter in diagnosing and treating COVID-19-induced bradycardia and GBS during the pandemic outbreak. However, the patient outcomes with the treatment combining the conventional treatment with therapeutic plasma exchange seem to be optimistic.